It does not gets more complicated than this

Algebra Level 5

Find the values of x for which the 6th term of

( 2 l o g ( 10 3 x ) + 5 2 ( x 2 ) l o g 3 ) m (\sqrt{2^{log(10 - 3^{x})}} + {}^{5}\sqrt{2^{(x - 2)log3}})^{m} where m €N is equal to 21 and the bimomial coefficients of the 2nd, 3rd and 4th terms are the first, third and the fifth terms of an A.P.

NOTE => x will have two values a and b where a and b are integers Give your answer in form of a+b.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Nov 23, 2014

It is suspected that m = 7 m=7 so that the 6 t h 6^{th} term will be as follows with the square and fifth roots removed:

( 7 5 ) ( 2 log ( 10 3 x ) ) 2 ( 2 ( x 2 ) log 3 5 ) 5 = 21 ( 2 log ( 10 3 x ) ) ( 2 ( x 2 ) log 3 ) \begin{pmatrix} 7 \\ 5 \end{pmatrix} (\sqrt{2^{\log{(10-3^x)}}})^2 (\sqrt [5] { 2^ { (x-2)\log {3} }})^5 = 21 (2^{\log{(10-3^x)}}) (2^ { (x-2)\log {3} })

It is in fact, m = 7 m = 7 , because the 2 n d 2^{nd} , 3 r d 3^{rd} and 4 t h 4^{th} coefficients are 7 7 , 21 21 and 35 35 , which are the 1 s t 1^{st} , 3 r d 3^{rd} and 5 t h 5^{th} of an A . P . A.P. with a common difference of 7 7 .

Now, we have, the 6 t h 6^{th} term equals to 21 21 :

21 ( 2 log ( 10 3 x ) ) ( 2 ( x 2 ) log 3 ) = 21 ( 2 log ( 10 3 x ) ) ( 2 ( x 2 ) log 3 ) = 1 \Rightarrow 21 (2^{\log{(10-3^x)}}) (2^ { (x-2)\log {3} }) = 21 \quad \Rightarrow (2^{\log{(10-3^x)}}) (2^ { (x-2)\log {3} }) = 1

log ( 10 3 x ) + ( x 2 ) log 3 = 0 log [ 3 ( x 2 ) ( 10 3 x ) ] = 0 \Rightarrow \log{(10-3^x)} + (x-2)\log {3} = 0 \quad \Rightarrow \log{[3^{(x-2)}(10-3^x)]} = 0

3 ( x 2 ) ( 10 3 x ) = 1 3 x ( 10 3 x ) = 9 10 ( 3 x ) 3 2 x = 9 \Rightarrow 3^{(x-2)}(10-3^x) = 1 \quad \Rightarrow 3^x(10-3^x) = 9 \quad \Rightarrow 10(3^x) -3^{2x} = 9

3 2 x 10 ( 3 x ) + 9 = 0 ( 3 x 1 ) ( 3 x 9 ) = 0 \Rightarrow 3^{2x} - 10(3^x) + 9 = 0 \quad \Rightarrow (3^x - 1)(3^x - 9) = 0

3 x = 1 \Rightarrow 3^x = 1 or 9 x = 0 9\quad \Rightarrow x = 0 or 2 2

Therefore, the required answer a + b = 0 + 2 = 2 a+b=0+2=\boxed {2}

Ayush Garg
Apr 16, 2015

Same solution as Chew seong cheong... Can anyone explain to me how and why reward points change for a question after every attempt.?

Fox To-ong
Jan 7, 2015

a =2, b = 0 sum = 0 + 2 = 2

You directly did it with hit and trial right ????

Aditya Tiwari - 6 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...